Perubahan Hukum Dengan Sebab Berubahnya Masa, Tempat dan Keadaan - Abdul Muthalib (Hikmah, 2018)
Legal Changes With The Cause of Time, Place and State This study aims to explore the ulama's view of the change of Islamic law by changing the times, places and circumstances. the renewal of Islamic law can be interpreted as an effort and deed through a certain process with full seriousness done by those who have the competence and authority in the development of Islamic law (Mujtahid) in ways that have been determined based on the rules of law istinbat justified making the Islamic law more fresh and modern, not out of date. This is what Ushul fiqh terminology is known as "Ijtihad".Keywords: Fiqh, Ijtihad, Legal Update.